ASSESSMENT OF ENERGY AND WATER AUDIT OF SELECTED SCHOOL OF AHMEDABAD (International Association of Biologicals and Computational Digest, 2023)
Climate change is one of the most significant environmental and societal issues of our time. This increase in temperature would have catastrophic consequences for the planet. To mitigate the impacts of climate change, urgent action is required at both the individual and societal levels. Energy audit is an essential process of identifying, analyzing, and evaluating the energy consumption patterns of a building or facility. Water audit is the process of analyzing water usage and identifying opportunities for conservation and efficiency improvements. A water audit can help individuals and organizations understand how much water they are using, this general structure of the energy assessment has undergone a few changes, It includes collecting data on water usage, identifying leaks and inefficiencies, and implementing measures to reduce water waste Which Was Created By American Water Works Association (AWWA) And International Water Association (IWA) In 2000.
Keywords: Energy Audit, Energy conservation, Water Audit, Save Water